Chemical and Physical Quality Biscuits Substitution Pumpkin and Leaves Katuk - Berek, Theresia Dewi Kartini; Lestari, Retno Sri; Adam, Adriyanu (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Dependence on wheat flour is very high, so food diversification efforts must be made to reduce this dependence. Biscuits are a product made from wheat flour as the main ingredient, and they have the potential to be developed using pumpkin and Katuk leaves. This study aims to determine the chemical and physical quality of biscuits substituted for pumpkin, and Katuk leaves. This research was an experimental study with a completely randomized design (CRD), consisting of 3 treatments and one standard treatment, with three repetitions of each treatment, so there were 12 treatment units. Chemical quality includes energy, carbohydrate content, protein, fat, Fe, calcium, vitamin C, β- carotene, and vitamin A. Physical quality is assessed using diameter, thickness, and spread ratio). Data were analyzed using One Way Anova and Krusskal Tests Wallis. The results on the chemical quality of biscuits show a significant effect of substituting pumpkin and Katuk leaves on protein, calcium, zinc, Fe, β- carotene, and vitamin C levels in biscuits. However, fat and carbohydrate levels decreased for energy as the substitution of pumpkin and Katuk leaves increased. The physical quality of biscuits substituted for pumpkin and Katuk leaves shows that the diameter and thickness decrease as the percentage of substitutes for pumpkin and Katuk leaves increases. This situation causes the spread ratio (spread) to increase. This research concludes that substituting pumpkin and Katuk leaves in biscuits significantly affects the chemical and physical quality of the biscuits.